A quasi-experimental test of the effects of criminal justice involvement on later mental health - Craig, Jessica M. (Journal of experimental criminology, 2018)
While many criminological theories posit causal hypotheses, many studies fail to use methods that adequately address the three criteria of causality. This is particularly important when assessing the impact of criminal justice involvement on later outcomes. Due to practical and ethical concerns, it is challenging to randomize criminal sanctions, so quasi-experimental methods such as propensity score matching are often used to approximate a randomized design. Based on longitudinal data from the Cambridge Study in Delinquent Development, the current study used propensity score matching to investigate the extent to which convictions and/or incarcerations in the first two decades of life were related to adverse mental health during middle adulthood.